Investigation of islanding detection methods in hybrid AC/DC microgrids - Ng, Ming He (2016)
Distributed generations (DG) are emerging as one of the promising solutions to integrate various types of distributed renewable energy sources with the utility grid. With the rapid advancements of technologies, power industries are introducing microgrids to cater the high demand of better power quality efficiency and reliability by customers. Currently, the evolution of technology is introducing microgrids which incorporate of distributed generation into power industries. However, microgrids are not widely used yet due to the lack of standards and uniform compliance testing. Research and development for microgrids are being carried out in companies and universities to form a proper IEEE standard before making microgrids common in the market. This project will explore the various types of islanding detection methods to build a stronger foundation for microgrids. Islanding detection methods are classified into two mostly used groups; active and passive, where it detects if distribution generation continues to power a power station even when the main grid is not supplying any power. Passive methods do not usually affect the power quality but they have larger non-detection zones (NDZ), which eventually affects the system reliability. Active methods have smaller non-detection zones but it affects the power quality due to the injection of small disturbance pulses. In addition, this project will develop a prototype program to detect islanding conditions, providing user with simulations to mimic the real world applications using Matlab/Similink while exposing the user to the latest technology in the utility industries.